Barcelona conference on epigenetics and cancer 2015: Coding and non-coding functions of the genome. Issue 1 (2nd January 2016) - Corujo, David; Mas, Gloria; Malinverni, Roberto; Di Croce, Luciano; Buschbeck, Marcus
ABSTRACT: The Barcelona Conference on Epigenetics and Cancer (BCEC) entitled "Coding and Non-Coding functions of the Genome" took place October 29–30, 2015 in Barcelona. The 2015 BCEC was the third edition of a series of annual conferences jointly organized by 5 leading research centers in Barcelona together with B-Debate, an initiative of BioCat. Luciano Di Croce from the Center for Genomic Regulation and Marcus Buschbeck from the Josep Carreras Leukemia Research Institute put together the scientific program with a particular focus on the role of non-coding RNAs in enhancer regulation, epigenetic control by Polycomb complexes, histone variants, and nuclear organization. In one and a half days, 22 talks and 56 posters were presented to an audience of 215 participants.